Solar irradiation on vertical surfaces in Shah Alam / Nur Izzati Zaharah Mohamed Azam - Mohamed Azam, Nur Izzati Zaharah (2006)
The solar irradiation on four vertical surfaces facing North, East, South and West orientations, were measured at Shah Alam. The irradiation on the horizontal surface was also measured simultaneously. The results of the measurements were compared with the simulated data using the Perez Model. The R values (ratio of solar irradiation on a vertical surface to the solar irradiation on the horizontal) for each vertical surface were also determined. A square (cube) box made from plywood with a black painted surface was built to put all the pyranometers used in the experiments. The experimental set-up was placed in an unobstructed location. Measured data were then processed and analyzed using simple statistical method. Results were compared with a semi-empirical data that were determined using Perez Model based on 10 years measured data taken from Petaling Jaya meteorological station for measurement period from 1980 to 1989. The R values for North, East, South and West produced from the processed data are 0.20, 0.50, 0.16, and 0.21 respectively. Error analyses were done dn the R values and were found to be 0.07, 0.06, 0.11 and 0.15 for North, East, South and West orientations respectively. This study has shown that the Perez Model may still be used for estimating solar radiation in Malaysia if newer models are not created, since the estimation values are almost as close to the measured data.